Report of the Committee on Development of Bio-Fuel - Planning Commission (Planning Commission, 2001)
Oil provides energy for 95% of transportation and the demand of transport fuel continues to rise. the requirement of Motor Spirit is expected to grow from little over 7 MMT in 2001 -02 to over 10 MMT in 2006-07 and 12.848 MMT in 2011-12 and that of diesel (HSD) from 39.815 MMT in 2001-02 to 52.324 MMT in 2006-07 and just over 66 MMT in 2011-12. the domestic supply of crude will satisfy only about 22% of the demand and the rest will have to be met from imported crude. Our dependence on import of oil will continue to increase in the foreseeable future.
Planning Commission Government of India
Planning Commission Government of India